2008
DOI: 10.1111/j.1095-8649.2008.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and the colonization of new territories by Chromis viridis

Abstract: The settlement and recruitment patterns of Chromis viridis were followed during three consecutive seasons along the reefs of Eilat, Red Sea. The findings, based on intensive field surveys and a translocation experiment, indicated a strong and repeatable preference for some, but not other, colonies of the branching coral Acropora eurystoma; with significantly more larvae settling onto preferred colonies that house conspecific adults and juveniles. Furthermore, these findings showed that, given high recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The temporal consistency in the response to specific colonies (see also Ben-Tzvi et al 2008), as well as its apparent generality among fish species and geographic location, suggests that the information conveyed by the cue(s) may relate to future prospects and not just immediate conditions. However, juvenile and adult C. viridis are known, at times, to emigrate away from their initial settlement sites and occupy SH-colonies (Ben-Tzvi et al 2008). This would seem to suggest a short-term benefit to microhabitat selection and/or the loss of sensitivity to the chemical cue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The temporal consistency in the response to specific colonies (see also Ben-Tzvi et al 2008), as well as its apparent generality among fish species and geographic location, suggests that the information conveyed by the cue(s) may relate to future prospects and not just immediate conditions. However, juvenile and adult C. viridis are known, at times, to emigrate away from their initial settlement sites and occupy SH-colonies (Ben-Tzvi et al 2008). This would seem to suggest a short-term benefit to microhabitat selection and/or the loss of sensitivity to the chemical cue.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Ben-Tzvi et al 2008), we have shown that settling Chromis viridis (Cuvier) prefer to settle with conspecific adults within Acropora spp. colonies (see also Lecchini et al 2005b).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 91%
See 3 more Smart Citations